Analysis of Factors Affecting the Formation of Current Patterns of Behavior in Behavioral Setting (Case Study: Azadi Square in Kermanshah) - Mostafa Shahinifar (تحقیقات کاربردی علوم جغرافیایی)
Urban public spaces have become increasingly vital in the functioning of cities, serving as primary sites for citizen interactions. These spaces play a significant role in understanding human behavior and in shaping behavioral settings. This article examines the factors that influence the establishment of behavioral patterns in Azadi Square, the main square in Kermanshah. Despite its communicative function, the social role of this square remains limited. The research conducted for this article employed a descriptive and survey-based methodology. Data collection techniques included observation, photography, face-to-face interactions, and physical presence within the study area. Additionally, interviews were conducted with randomly selected individuals based on pedestrian flow in the square. Each interview lasted an average of approximately 12 minutes. Analysis of behavioral pattern maps in the area revealed a mismatch between the form and function of Azadi Square. Dynamic and static activities within the square were of short duration, while the haphazard arrangement of details hindered its visual expression. The lack of human-scale dimensions in the space resulted in a decline in quality for activities such as meetings, exercise, play, sitting, stopping, and even walking. Overall, the quality of Azadi Square in Kermanshah has not adequately met the functional needs of its users. Consequently, this research emphasizes the importance of understanding the relationship between behavioral patterns and the environment, enabling designers to enhance the quality of such spaces.